Two decades of biotechnology research in plantation breeding: A systematic review - Hakim, A R; Putranto, R A (IOP conference series. Earth and environmental science, 2022)
Riset Perkebunan Nusantara (RPN) has been carried out diverse research activities in plantation breeding for years. It has been a common understanding that the current biotechnology approach cannot be separated from plant breeding research. However, there has never been any review on research topic trends in RPN. This research was conducted to test the systematic review methodology upon a public database in the biotechnology approach implemented in plant breeding research. This systematic review was carried out on the research conducted by RPN over the last two decades published in global scientific papers. Surveys and screening of scientific papers were carried out using the PRISMA protocol to objectively obtain related research subjects. The survey traced 7,691 records from Google Scholar using specific keywords searches in which 4,041 scientific papers were obtained. The screening process retained 73 scientific papers related to RPN’s historical roadmap for plant breeding using biotechnology. The highest number of publications was achieved in 2018 followed by a decrease in the number of publications until 2021. When viewed from the commodity, 26 of the total 73 selected records were studies on oil palm commodities followed by 19 on rubber trees and 10 on cocoa.